Discordant placental oxygenation and autophagy in twin anemia-polycythemia sequence (TAPS) - Mao, Quanfu (Placenta, 2019)
BACKGROUND: (Macro)autophagy is an important process of self-degradation of macromolecules and organelles that ensures cellular homeostasis and energy preservation during stressful conditions. Dysregulated placental autophagy has been implicated in a wide range of pregnancy complications. Recent studies identified hypoxia as a key regulator of trophoblast autophagy in vitro; however, its effects on placental autophagy in vivo remain incompletely understood. In this study, we evaluated the monochorionic twin anemia-polycythemia sequence (TAPS) placenta as model of discordant placental oxygenation to determine the effects of hypoxia on placental autophagy in utero. METHODS: We performed a retrospective comparative analysis of tissue oxygenation and autophagy in anemic and polycythemic territories of TAPS placentas (N = 12). Archival tissues were subjected to immunohistochemical, immunofluorescence and Western blot analyses of carbonic anhydrase (CA) IX (hypoxia marker) and key autophagy/lysosomal markers. RESULTS: CAIX protein levels were significantly higher in anemic twin territories than in corresponding polycythemic territories, consistent with relative tissue hypoxia. Anemic placental shares further displayed significantly higher levels of LC3I/II (autophagosome markers) and LAMP1/2 (lysosome markers), associated with upregulated expression of lysosome/autophagosome activity-associated markers, transcription factor EB and cathepsin D. The accumulation of autophagosomes and lysosomes in anemic shares was accompanied by elevated p62 protein expression, suggestive of inhibition of the downstream autophagy pathway. CONCLUSIONS: TAPS placentas display striking intertwin discordance in tissue oxygenation and autophagic activity and may provide a suitable model for study of the interrelationship between hypoxia, autophagy, and pregnancy outcome in a monochorionic twin setting.